2016
DOI: 10.1155/2016/6045894
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of 18F-FLT PET/CT in Pediatric Lymphoma

Abstract: We performed an observational pilot study of 18F-FLT PET/CT in pediatric lymphoma. Eight patients with equivocal 18F-FDG PET/CT underwent imaging with 18F-FLT PET/CT. No immediate adverse reactions to 18F-FLT were observed. Compared to 18F-FDG, 18F-FLT uptake was significantly higher in bone marrow and liver (18F-FLT SUV 8.6 ± 0.6 and 5.0 ± 0.3, versus 18F-FDG SUV 1.9 ± 0.1 and 3.4 ± 0.7, resp., p < 0.05). In total, 15 lesions were evaluated with average 18F-FDG and 18F-FLT SUVs of 2.6 ± 0.1 and 2.0 ± 0.4, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…When using 11 C-MET, SUV max did not significantly differ between both groups, although it tended to be lower in patients with GBM have not yet been reported to be appropriate tools for investigating PCNSL. 2,23 The 68 Ga-pentixafor, which is a tracer binding to the CXCR4 chemokine receptor, was similarly used for investigating GBM 24 and PCNSL, 25 whereas no study to date compared its uptake in both tumor types. We can therefore conclude that, by combining advanced MRI sequences with using a PET radiopharmaceutical, either 18 F-FDG or 11 C-MET, PCNSL differentiation from other brain malignancies could be rendered possible, with high probability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When using 11 C-MET, SUV max did not significantly differ between both groups, although it tended to be lower in patients with GBM have not yet been reported to be appropriate tools for investigating PCNSL. 2,23 The 68 Ga-pentixafor, which is a tracer binding to the CXCR4 chemokine receptor, was similarly used for investigating GBM 24 and PCNSL, 25 whereas no study to date compared its uptake in both tumor types. We can therefore conclude that, by combining advanced MRI sequences with using a PET radiopharmaceutical, either 18 F-FDG or 11 C-MET, PCNSL differentiation from other brain malignancies could be rendered possible, with high probability.…”
Section: Discussionmentioning
confidence: 99%
“…Other radiopharmaceuticals in use for the investigation of brain tumors ( 18 F-thymidine [ 18 F-FLT], 18 F-fluorodopa [ 18 F-DOPA], 18 F-fluoroethyl-L tyrosine [ 18 F-FET]) have not yet been reported to be appropriate tools for investigating PCNSL 2,23 . The 68 Ga-pentixafor, which is a tracer binding to the CXCR4 chemokine receptor, was similarly used for investigating GBM 24 and PCNSL, 25 whereas no study to date compared its uptake in both tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…76,77 Its use as a biomarker in childhood cancer is mostly limited to preclinical models of glioma, 78,79 Ewing sarcoma, 80 and rhabdomosarcoma, 81 and a pilot study of 18 F-FLT uptake in pediatric patients with lymphoma. 82 Conceivably, uptake of this tracer might be a superior response biomarker for agents that primarily act by arresting cell proliferation, such as with CDK4/6 inhibitors. 83 In fact, changes in 18 In our experiments, selumetinib was able to slow tumor growth whereas trametinib did not-even though each drug suppressed phospho-ERK1/2.…”
Section: Discussionmentioning
confidence: 99%
“…Although not all clinical trials have shown a one‐to‐one correlation with cell proliferation, increased 18 F‐FLT uptake seems to correlate at least as well as 18 F‐FDG with unfavorable outcomes 76,77 . Its use as a biomarker in childhood cancer is mostly limited to preclinical models of glioma, 78,79 Ewing sarcoma, 80 and rhabdomosarcoma, 81 and a pilot study of 18 F‐FLT uptake in pediatric patients with lymphoma 82 . Conceivably, uptake of this tracer might be a superior response biomarker for agents that primarily act by arresting cell proliferation, such as with CDK4/6 inhibitors 83 .…”
Section: Discussionmentioning
confidence: 99%
“…blizn wywołanych terapią), co umożliwia dokładniejsze określenie rokowania [19]. W przypadku badań radioizotopowych istnieje jednak ryzyko wyniku fałszywie dodatniego lub fałszywie ujemnego ze względu na fizjologiczne wysokie gromadzenie radioznacznika w grasicy oraz w obszarach intensywnego wzrostu kości [20].…”
Section: • Chłoniak Złośliwyunclassified